2002
DOI: 10.1046/j.1365-2702.2002.00597.x
|View full text |Cite
|
Sign up to set email alerts
|

Role boundaries – research nurse or clinical nurse specialist? A literature review

Abstract: This paper focuses on issues relating to the role components of clinical nurse specialists and clinical research nurses working in breast cancer care. Identified issues relate to the lack of agreement as to the role and definition of clinical nurse specialists. At the same time there has been an increase and emergence of clinical research nurses, both within the NHS and university departments. The review fails to reveal the relationship between these two specialist groups in terms of role overlap and role boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…The dilemma of whether or not M‐level nurses should be responsible for conducting research is also reflected in the broader literature (Drennan 2007; Raja‐Jones 2002). Although the researcher's role is widely considered to be a core aspect of advanced practice, Read et al.…”
Section: Discussionmentioning
confidence: 99%
“…The dilemma of whether or not M‐level nurses should be responsible for conducting research is also reflected in the broader literature (Drennan 2007; Raja‐Jones 2002). Although the researcher's role is widely considered to be a core aspect of advanced practice, Read et al.…”
Section: Discussionmentioning
confidence: 99%
“…No UK studies of the CRN role were found. However, commentaries highlight a gap in understanding of the role, its scope and potential contribution to clinical trials (Raja‐Jones 2002, Stephens‐Lloyd 2004). We were aware of the growing number of studies evaluating the development of ‘specialist’ and ‘advanced’ roles for nurses – including clinical nurse specialists, nurse practitioners, advanced nurse practitioners, consultant nurses – which can also incorporate a research component.…”
Section: Introductionmentioning
confidence: 99%
“…Formal orientation and mentorship programmes are rare for clinical nurse educators and often their socialization into the role is haphazard and serendipitous (Youngstrom 1996). Further, the blurring of role boundaries and responsibility between clinical nurse educators, clinical nurse specialists, and research nurses has led to role ambiguity and poor productivity among these specialized groups of nurses (Mackay 1998; Mateo & Fahje 1998; Raja‐Jones 2002). Consequently, many challenges face clinical nurse educators who are involved in ensuring that research constitutes the basis for practice.…”
Section: Introductionmentioning
confidence: 99%